Affordable Rapid Olfaction Measurement Array: A Novel, Essential Oil-Based Test Strongly Correlated with UPSIT and Subjective Outcome Measures. (January 2020) - Villwock, Jennifer A.; Li, Jennifer; Moore, Chelsea; Chiu, Alexander G.; Sykes, Kevin J.
Background: Olfactory dysfunction is an important facet of numerous disease states ranging from sinonasal disease to neurocognitive disorders. Due to expense and/or logistical barriers, objective olfactory testing is not common. We describe the creation of a novel, essential oil-based smell test, A ffordableR apidO lfactionM easurementA rray (AROMA), composed at 14 scents at different concentrations and demonstrate correlation of AROMA with the University of Pennsylvania Smell Identification Test (UPSIT), patient age, Sinonasal Outcomes Test (SNOT-22), and perceived loss of smell. Methods: AROMA was developed for point-of-care olfactory testing and compared to the UPSIT, as well as subjective outcome measures as noted above. About 37 healthy controls were prospectively recruited to assess the reliability of AROMA using a test–retest protocol. An additional cohort of 38 participants with sinonasal disease were prospectively recruited to complete the AROMA and UPSIT, and were compared with a cohort of 30 healthy controls. Spearman correlation correlated AROMA and UPSIT results, patient age, SNOT-22, and perceived loss of smell. Results: AROMA demonstrated good test–retest reliability ( r = 0.85, P < .001). Spearman's rho correlation of AROMA to UPSIT was statistically significant at ρ = 0.75 ( P < .001). SNOT-22, age, and perceived sense of smell were all significantly correlated with both AROMA (ρ = −0.548, −0.557, −0.642, respectively) and UPSIT (ρ = −0.367, −0.460, −0.552, respectively). Conclusion: AROMA has a strong correlation with UPSIT and may be more strongly correlated with sinonasal outcomes. Additionally, AROMA is reusable; level of odorant is not static; and AROMA can test both odor detection and identification. Level of evidence: 2b